Research on the bearing characteristics of brackets in thick hard roof mining sites and the effect of blasting on roof control - Jiaxin Dang; Min Tu; Xiangyang Zhang; Qingwei Bu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2024)
Abstract Deep mining stress increase and thick hard rock layer endowment drive rock body fissure expansion, leading to sudden fracture of the roof plate accidents. The roof slab of 11,129 working face in Zhangji Mine is a 16 m thick sandstone composite roof slab, whose compressive strength reaches 89.8 MPa. The hardness of the roof slab is high, its bearing capacity is high, and it is difficult to collapse. The hardness of the roof plate is high, its bearing capacity is high, and it is difficult to fall. If the roof plate does not fall in time, it will lead to the energy accumulation of itself, and the sudden fracture and fall will make the working face and the two roadways show the drastic mine pressure, which will lead to the risk of the coal wall appearing the slice of gangs, the roof falling and the pressure frame. Therefore, for the 11,129 working face thick hard sandstone roof plate direct cover and mining technology conditions. It is very necessary and imperative to research the artificial roof release technology of deep hole pre-cracking blasting to improve the adventitious fall of the thick hard roof plate, reduce the overhanging roof area of the mining hollow area, and reduce the incoming pressure strength of the roof plate. This paper adopts the research method combining theory, physical experiment, numerical simulation and field test, focusing on research and analysis of the deflection change of the roof plate after pre-cracking and blasting, the relationship between the roof plate and the role of the bracket, and the effect of artificial blasting to release the roof. The results show that the theoretical part deduces and analyzes the relationship equation of the influence of the rotating and sinking of the roof plate on the pressure of the support, and combined with the law of the roof plate-support action can be divided into three stages: (1) Initial stage of mining, (2) Rotating and sinking stage, and (3) Breakdown and fragmentation stage. The deep stress increase and the rock layer's own characteristics (hardness and thickness) are the main controlling factors to determine the bearing capacity of the stent. As the depth of coal mining increases, the pressure at the minimum roof control distance of the stent gradually increases from 11.5 to 34.6 MPa. The increase of rock hardness relatively reduces the force acting on the stent, and the stent bearing capacity decreases by 75% when the hardness increases from 8 to 32 GPa. The 11,129 engineering geological parameters are brought into the calculation to obtain the pressure in the stent control distance of 13.5–20.5 MPa. The simulation part analyzes the stress relief degree of the roof plate before and after the roof blasting, and the peak stress in front of the coal wall is reduced from 46.7 to 30.9 MPa, which is an obvious effect of pressure relief, and the simulation results are analyzed in comparison with the theoretical results to validate the reliability of the simulation results. Further, the physical similarity experiments were conducted to analyze the deformation behavior of mining instability and crack evolution characteristics of the overburden rock of the quarry after cutting the roof, and the peak stress of the coal wall was in the range of 22.7–27.8 MPa after the blasting decompression, which was mutually verified with the theoretical analysis and the simulation results to ensure the reliability of the calculation results. Combined with the geological conditions of the mine area, the "fan-shaped" blasting hole arrangement is proposed to carry out segmental blasting, and the specific parameters of different locations of the holes are given. The effect of pre-cracking blasting was examined, and it was found that the rock mass at the hole opening had a high degree of fragmentation, and the ring and strike cracks appeared alternately in the middle and lower part of the drilling holes, and the polygonal energy slit played a very effective role, and achieved the purpose of artificially releasing the roof. At the same time, it is improved the load-bearing environment of the mining support, which further improves the safety and efficiency production of the coal mine.